2019
DOI: 10.3390/antiox8120603
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Remodelling: An Accomplice for New Therapeutic Strategies to Fight Lung Cancer

Abstract: Metabolic remodelling is a hallmark of cancer, however little has been unravelled in its role in chemoresistance, which is a major hurdle to cancer control. Lung cancer is a leading cause of death by cancer, mainly due to the diagnosis at an advanced stage and to the development of resistance to therapy. Targeted therapeutic agents combined with comprehensive drugs are commonly used to treat lung cancer. However, resistance mechanisms are difficult to avoid. In this review, we will address some of those therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 222 publications
(312 reference statements)
0
16
0
Order By: Relevance
“…Chemoresistant cancer cells become highly adapted to intrinsic or drug-induced oxitive stress by upregulating their antioxidant systems [ 22 , 23 ] ( Figure 2 ). In a recent review, Sferrazzo et al reported that HO-1 overexpression is involved in chemotherapy and radiotherapy resistance of brain tumors such as neuroblastoma, medulloblastoma, meningioma, and astrocytoma [ 24 ].…”
Section: Oxidative Stress and Chemoresistancementioning
confidence: 99%
“…Chemoresistant cancer cells become highly adapted to intrinsic or drug-induced oxitive stress by upregulating their antioxidant systems [ 22 , 23 ] ( Figure 2 ). In a recent review, Sferrazzo et al reported that HO-1 overexpression is involved in chemotherapy and radiotherapy resistance of brain tumors such as neuroblastoma, medulloblastoma, meningioma, and astrocytoma [ 24 ].…”
Section: Oxidative Stress and Chemoresistancementioning
confidence: 99%
“…These changes allow them to meet the requirements of the rapid cell division and to avoid signals that would lead to their growth arrest and execution, such as apoptotic signals [7,9,10]. Among the metabolic alterations observed in lung cancer, those associated with lipid metabolism have recently received increasing attention and recognition [11]. In this review, we explored the role of lipid metabolic rewiring in lung cancer development and progression and in resistance to therapies, focusing in particular on its connection with EGFR signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular stress responses are bioenergetically demanding as a suite of stress proteins need to be synthesized de nova in large quantities [26][27][28][29][30][31] . As a result, cells may enter a survival mode where they undergo global translational and metabolic reprogramming to preserve and divert energy for the stress response while specialized cell functions may be compromised 32,33 . Therefore, the onset of adaptive transcriptional stress control, for the purpose of cell survival, may be regarded as the onset of functional adversity.…”
Section: Introductionmentioning
confidence: 99%